Study of Ignatius of Anthiochâ€™s Letter to the Epphesian in Ecumenical Church Today - Dewantara, Agustinus Wisnu (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2024)
Abstract: GerejaChurch life is bound up in a sense of togetherness. All members of the Church are bound together in one family in the faith. This research focuses on examining the idea ofCoinonia (communion) initiated by Ignasius of Antioch. The primary source is taken from Ignatius of Antioch's letter to the church at Ephesus. Ignatius of Antioch's letter to the church at Ephesus is an entry point to understanding how the church at that time fellowshipped and united. It turns out that the challenge of unity has existed since ancient times, and continues to this day in different forms. This research uses text analysis methods. Excavating documents and writings from Ignasus Anthiokia as one of the Church Fathers needs to be explored to capture how post-apostolic post-apostolic post-apostolic ideology was understood and practiced. This article seeks to contribute to the exploration of the theme of koinonia initiated by the Church Fathers, and to draw out its relevance for the appreciation of communion today. The conclusion that can be drawn is how important it is to maintain a sense of unity in faith as a form of koinonia amidst today's current of individualism, while remaining open to a variety of thoughts.Â Keywords: Coinonia (togetherness), Ignatius of Antioch, Ephesus. People, Church